Estimating real time individual lysine and threonine requirements in precision-fed pigs - Remus, A. [UNESP]; Methot, S.; Hauschild, L. [UNESP]; Letourneau-Montminy, M. P.; Pomar, C. [UNESP]; Chizzotti, M. L. (Wageningen Acad Publ, 2019)
This study aimed to estimate independently real-time lysine (Lys) and threonine (Thr) requirements in growing-finishing pigs. Ninety-five pigs were randomly assigned to treatments according to 2x5 factorial arrangement with 2 amino acids (AA; Lys, and Thr) and 5 levels of incorporation (60, 80, 100, 120 and 140% of the estimated requirements) as main factors. Lysine and Thr requirements were estimated daily in real time during a 21-day trial. Data was analyzed using LOESS regression and the surface response methodology. The point of maximum response was obtained through a canonical analysis of the adjusted response surface and was found to be saddle-shaped, possibly due to the variability within AA requirements among individual pigs and thus pointed for several possible optimal Thr/Lys combinations. In conclusion, the non-unique response of the regression model indicates that there is a large between-animal variation in protein deposition (PD) response to Lys and Thr supply.
Keywords: threonine; lysine; precision feeding; precision livestock farming